Perceptions of nursing students after performing an individual activity designed to develop their critical thinking: The "critical card" tool. (March 2018) - Urcola-Pardo, Fernando; Blázquez-Ornat, Isabel; Anguas-Gracia, Ana; Gasch-Gallen, Ángel; Germán-Bes, Concepción
Abstract: Critical thinking in Health Sciences is among the transversal competences in the Nursing Degree. The critical card is a tool of individual learning, designed to develop critical thinking, and set in the process of environmental health learning. Every student must perform the activity to obtain the highest qualification in Community Health Nursing subject. The aim of this project was to evaluate this learning tool using the students' perceptions after its performance. The evaluation was based on the answers to a questionnaire obtained from the third course students of Nursing Degree at the University of Zaragoza. The questionnaire was made up of 14 Likert-type questions, grouped in four dimensions. The student participation rate was higher than 50%. The analysis of the questionnaire obtained 67, 8% positive answers. The variability between dimensions ranged between 49% of positive answers for application in other subjects and 87% of positive answers for the improvements applicable to the instrument. The students coincided in indicating that the critical card is a useful learning tool and could be applicable in other subjects. However, the weight it is given in the global evaluation of the subject is considered to be too low, considering the time used to complete the activity. Highlights: Perform the critical card allows the student's critical thinking development. The free choice of the theme increases the involvement with carrying out the work. It's necessary to balance the time used with the weight given in the qualifications.